2005
DOI: 10.1055/s-2004-830358
|View full text |Cite
|
Sign up to set email alerts
|

Report of an Uncommon Cluster of Septic Arthritis of the Hip in Premature Newborns: Three Cases in a Period of 3 Months

Abstract: We report an uncommon cluster of this rare condition which occurred within a very short period of time in our unit. We reviewed the current literature and observed that the diagnosis is often delayed, which can have very serious consequences for the outcome. Our 3 patients have had an uncomplicated course so far and follow-up examination at almost one year was normal. A high index of suspicion for the diagnosis and early and aggressive treatment is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Velkes et al [15] reported two cases of negative arthrosonograms that were caused by spontaneous capsular perforation and extra-articular drainage of the effusion. Kaczala et al [13] described similar cases in neonates, in whom effusion was absent because the capsule was destroyed. Since our results are based on cases in which aspiration was performed 2-24 days after symptom onset, results varied from cases diagnosed in the very early stages of disease.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Velkes et al [15] reported two cases of negative arthrosonograms that were caused by spontaneous capsular perforation and extra-articular drainage of the effusion. Kaczala et al [13] described similar cases in neonates, in whom effusion was absent because the capsule was destroyed. Since our results are based on cases in which aspiration was performed 2-24 days after symptom onset, results varied from cases diagnosed in the very early stages of disease.…”
Section: Discussionmentioning
confidence: 90%
“…Kaczala et al . [13] described similar cases in neonates, in whom effusion was absent because the capsule was destroyed. Since our results are based on cases in which aspiration was performed 2–24 days after symptom onset, results varied from cases diagnosed in the very early stages of disease.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations